Health justice : an argument from the capabilities approach - Venkatapuram, Sridhar (Cambridge, U.K. : Polity, 2011)
'Recognizing the social bases of health and longevity, Venkatapuram extends the'capabilities approach' of Amartya Sen and Martha Nussbaum into the domain of health and health sciences. ...He formulates an inter-disciplinary argument that draws on the natural and social sciences... to argue for every human being's moral entitlement to a capability to be healthy.'
Includes bibliographical references (p. 247-264) and index.
Keywords: Right to health; Social justice; Public health -- Moral and ethical aspects